The PEC-G and University Internationalization - Macedo, Maria do Socorro Alencar Nunes; Gomides, Paula Aparecida Diniz (Debates em Educação, 2020)
This article presents a broader research clipping that aimed to understand the strategies and trajectories of foreign undergraduate students at a Brazilian public university. In this text we focus on the PEC-G (Undergraduate Student Agreement Program) and the relationships established by African students linked to this program as an internationalization and academic mobility policy. Based on some concepts of Bourdieu, we seek to understand the meanings attributed by students to the educational process in Brazil and their expectations with the conclusion of the course. Based on assumptions of qualitative research, we produced two different types of data, the interview being the main source. Fourteen students and the university's international affairs advisor were interviewed. Another source of data were the documents on the MRE (Ministry of Foreign Affairs) and MEC (Ministry of Education) websites that characterize the PEC-G. The results indicate that it is necessary to engage these young students and assist them in their specificities, both in academic education and in cultural and critical education. This service goes through a quality reception that provides relevant information and really helps them to make the most of the experience in our country.